Public Sector Audit Practices and Accountability in Nigeria - Sani Abdullahi Shinkaf (Journal of Accounting and Financial Management, 2026)
This study examines public sector audit practices and accountability in Nigeria, focusing on Zamfara State. It examines how audit independence, accuracy of financial reporting, compliance with standards, transparency, and credibility reporting affect accountability in public institutions. A survey research design was employed, and data were collected from 300 auditors selected from ministries, departments, and agencies through multistage sampling. Descriptive and regression analyses were used for data interpretation. The ANOVA results in Table 4.1. shows that good governance does not significantly influence public audit transparency and its impact on accountability in Zamfara State. The regression sum of squares was 21.157, while the residual sum of squares was 54,549.760, yielding a total of 54,570.917. The model produced an F-value of 0.023 with a significance level of 0.0256. Since the p-value is less than the 0.05 threshold, the result is statistically significant, indicating that audit transparency and accountability contribute meaningfully to explaining variations in good governance within the state. The findings revealed that audit independence and accuracy of financial reporting have no significant impact on accountability, while audit compliance with standards, transparency, and credibility reporting significantly influence accountability. The study concludes that strengthening audit processes and ensuring adherence to standards are crucial for improving accountability in Nigeria’s public sector.